Cr2O3 / TiO2 / BC photocatalyst and preparation method thereof
By combining the chromium-titanium coordination compound with skin collagen fibers and pyrolyzed on biochar, the existing photocatalyst has been solved, and efficient and stable photocatalytic degradation effect has been achieved.
Patent Information
- Application Number
- CN202310137561.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-02-20
AI Technical Summary
In the preparation and application of existing TiO2/MO photocatalysts, such as small specific surface area, metal ion agglomeration and metal ion leakage, resulting in low catalytic reaction activity and unstable.
By combining the chromium-titanium coordination compound with the skin collagen fibers, a Cr2O3/TiO2/BC photocatalyst was formed and pyrolytic treatment was carried out under an inert gas atmosphere to stabilize the loading of chromium-titanium bimetal on biochar.
The specific surface area and photocatalytic activity of the photocatalyst are improved, the degradation ability of organic pollutants in wastewater is enhanced, and the stability and cycle stability of the catalyst are significantly improved.
Smart Images

Figure CN116196915B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysts, and in particular to a Cr2O3 / TiO2 / BC photocatalyst and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of society, tetracycline-containing wastewater has become one of the main sources of water pollution. At present, photocatalytic degradation has become one of the important methods for removing organic pollutants in wastewater due to its advantages of no secondary pollution, high efficiency and low cost.
[0003] The most widely studied photocatalyst in the photocatalytic method is TiO2, because it has the characteristics of non-toxicity and low cost. However, the photogenerated electrons and holes of pure TiO2 photocatalysts are easy to recombine, the separation efficiency is low, and the photodegradation ability is limited. Therefore, in order to improve the photocatalytic degradation ability of TiO2 photocatalysts, researchers have combined TiO2 with other metal oxides (MO) to form heterojunction photocatalysts, thereby improving the utilization efficiency of photogenerated electrons and holes. However, directly compounding TiO2 with MO will result in a small specific surface area of the prepared composite material, and metal ion agglomeration may also occur, which is not conducive to improving the catalytic reaction activity. In order to avoid the above problems, some researchers have loaded TiO2 and MO on the surface of activated carbon or biochar, but this may lead to metal ion leakage and secondary pollution. To solve this problem, the existing technology adopts a solution that uses the metal organic framework MIL-101 (Cr) as a template to grow TiO2 particles on the surface to prepare Cr2O3 / C@TiO2 core-shell composite materials. This composite material has excellent photocatalytic performance and has stronger photocatalytic activity than pure TiO2, but this loading method is unstable and has the problem of metal ion leakage, making it difficult to be widely used in practical applications. Therefore, it is urgent to study a method for stably loading multiple metal ions on a carbon source. Summary of the invention
[0004] In response to the problems existing in the preparation and application of TiO2 / MO photocatalysts in the above prior art, the present invention provides a Cr2O3 / TiO2 / BC photocatalyst and a preparation method thereof, which can stably and evenly fix multiple metals on a carbon source and has good practical application prospects.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The preparation method of Cr2O3 / TiO2 / BC photocatalyst comprises the following steps:
[0007] Adding a chromium-titanium coordination compound to the pretreated leather powder for tanning, washing and drying the tanned leather powder to obtain a chromium-titanium bimetallic leather powder; and
[0008] The chromium-titanium bimetallic skin powder is placed in an inert gas atmosphere for two pyrolysis steps and then washed and dried.
[0009] Preferably, the method for pretreating the leather powder is: soaking the leather powder in deionized water for 6 to 12 hours to obtain a leather powder mixed solution.
[0010] Preferably, the mass ratio of the leather powder to the chromium-titanium coordination compound is 1:(1-2.7).
[0011] Preferably, the specific method of performing the two pyrolysis is: placing the loaded chromium-titanium bimetallic skin powder in an inert gas atmosphere at 300-500°C for 2 h, and after activation treatment, pyrolyzing it at 700-900°C for 2 h.
[0012] Preferably, the activation treatment is performed using a 2-4 mol / L KOH solution.
[0013] Preferably, the preparation method of the chromium-titanium coordination compound is: after dissolving chromium sulfate and titanium sulfate, adding sodium formate, adjusting the pH to 2.0-3.0, reacting at 50-70° C. for 1-2 h, and drying.
[0014] Preferably, the molar ratio of chromium sulfate, titanium sulfate and sodium formate is 1: (1-2.5): (0.2-1).
[0015] Preferably, the tanning temperature is 30-40°C, the tanning time is 2-4 h, and the pH is 3.5-4.5.
[0016] Preferably, the tanned leather powder is washed with deionized water and ethanol alternately to remove the tanning liquid, and dried at 30-40°C.
[0017] The invention also discloses a Cr2O3 / TiO2 / BC photocatalyst obtained by any of the above preparation methods.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention regulates the mixing conditions of chromium sulfate and titanium sulfate, which is conducive to the formation of a uniform heteronuclear hydroxyl bridge complex between the two, and then utilizes the reactive groups (such as -COOH, -NH2, -OH, etc.) exposed on the collagen to form coordination bonds with the chromium-titanium coordination complex, so that the two metal ions can be more evenly and stably loaded on the biochar. At the same time, biochar not only has a large specific surface area and is more fully in contact with pollutants, but also can be used as a carrier for electron transfer, accelerating the separation efficiency of photogenerated electrons and holes, thereby improving the photocatalytic activity.
[0020] 2. The photocatalyst prepared by the present invention has the advantages of high stability, strong photocatalytic activity and excellent cycle stability, and has good degradation performance for organic pollutants in wastewater. At the same time, the present invention uses waste skin collagen fiber biomass as raw material, providing a way of waste resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the SEM image of the catalyst of Examples 1 to 3 of the present invention;
[0022] Figure 2 1 is a BET diagram of the catalysts of Examples 1 to 3 of the present invention;
[0023] Figure 3 is the XRD diagram of the catalysts of Examples 1 to 3 of the present invention;
[0024] Figure 4 PL diagrams of catalysts of Examples 1 to 3 of the present invention;
[0025] Figure 5 It is a photocatalytic degradation effect diagram of tetracycline (TC) by pure TiO2 and catalysts of Examples 1 to 3 of the present invention;
[0026] Figure 6 It is a cycle test diagram of the catalyst of Embodiment 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0027] For a better understanding of the technical solution of the present invention, the technical solution of the present invention will be further described below in conjunction with the accompanying drawings and embodiments. The modes for implementing the present invention include but are not limited to the following embodiments, which are used to illustrate the present invention but are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. The test methods in the following embodiments, unless otherwise specified, are conventional methods.
[0028] The first embodiment of the present invention provides a method for preparing a Cr2O3 / TiO2 / BC photocatalyst, comprising the following steps:
[0029] Adding a chromium-titanium coordination compound to the pretreated leather powder for tanning, washing and drying the tanned leather powder to obtain a chromium-titanium bimetallic leather powder; and
[0030] The chromium-titanium bimetallic skin powder is placed in an inert gas atmosphere for two pyrolysis steps and then washed and dried.
[0031] The present invention adjusts the molar ratio between chromium sulfate and titanium sulfate, complexes Cr(III) and Ti(IV) into a chromium-titanium coordination compound, and coordinates and combines with reactive groups (such as -COOH, -NH2, -OH, etc.) on collagen, so that Cr(III) and Ti(IV) can be stably and evenly loaded on collagen. Then, a Cr2O3 / TiO2 / BC catalyst composite photocatalyst with a large specific surface area and excellent photocatalytic performance is prepared through high-temperature pyrolysis and calcination. The two metals of chromium and titanium can be stably loaded on biochar, and Cr2O3 and TiO2 form a bimetallic synergistic effect, which can enhance the catalytic activity.
[0032] The leather powder used in the embodiment of the present invention is obtained by crushing untanned waste leather scraps, and the mesh size is generally 40 meshes; in order to increase the hydrophilicity of collagen fibers in the leather powder, the leather powder needs to be soaked in deionized water for 6 to 12 hours to obtain a leather powder mixed solution, thereby completing the pretreatment of the leather powder. There is no need to specifically limit the amount of leather powder and deionized water used. For example, in some preferred embodiments, the mass ratio of leather powder to deionized water can be 1: (10 to 30).
[0033] In some preferred embodiments, the mass ratio of the leather powder to the chromium-titanium coordination compound is 1:(1-2.7).
[0034] The preparation method of the chromium-titanium coordination compound is as follows: after dissolving chromium sulfate and titanium sulfate, sodium formate is added, and the pH is adjusted to 2.0-3.0, the reaction is carried out at 50-70°C for 1-2 hours, and then the mixture is dried. The chromium sulfate and titanium sulfate can be dissolved in deionized water or in dilute sulfuric acid. Sodium formate is used as a masking agent; there is no particular limitation on the reagent for adjusting the pH, and formic acid and sodium bisulfite can be preferably used.
[0035] The molar ratio of chromium sulfate, titanium sulfate and sodium formate is controlled to be 1: (1-2.5): (0.2-1).
[0036] The specific method of performing two pyrolysis in the embodiment of the present invention is: placing the chromium-titanium bimetallic skin powder under an inert gas atmosphere at 300-500 ° C for 2 h, and after activation treatment, pyrolyzing at 700-900 ° C for 2 h. The inert gas atmosphere is a commonly used inert gas atmosphere, such as nitrogen. The activation treatment is also a commonly used activation method. In some preferred embodiments, a 2-4 mol / L KOH solution can be used for activation treatment.
[0037] When the chromium-titanium coordination compound is added to the pretreated leather powder for tanning, the tanning method used is a common tanning method. For example, in some preferred embodiments, the tanning temperature can be 30-40°C, the time is 2-4 hours, and the pH is 3.5-4.5. The tanned leather powder is washed with deionized water and ethanol alternately, and dried at 30-40°C.
[0038] In order to make the present invention clearer, the preparation and performance of the catalyst are described in detail using multiple specific implementation methods below.
[0039] It should be noted that the “parts” used in the following specific examples are all “parts by mass”.
[0040] Example 1: Preparation of Cr2O3 / TiO2 / BC catalyst
[0041] (1) Dissolve 20 parts of chromium sulfate and 21 parts of titanium sulfate (molar ratio 1:1) in deionized water, add 3 parts of sodium formate as a masking agent, add formic acid and sodium bisulfite solution to adjust the pH to 2.0-3.0, stir and react at 50-70 °C for 1-2 h, and dry to obtain a chromium-titanium coordination compound.
[0042] 15 parts of leather powder and 300 parts of deionized water were added to a three-necked flask and soaked for 12 hours. 30 parts of chromium-titanium coordination compound were completely dissolved in 200 parts of water and then added to the three-necked flask. The three-necked flask was placed in a 30 ℃ water bath and stirred continuously. After soaking for 1 hour, the pH of the tanning liquid was immediately adjusted to 2.0 with a saturated NaHCO3 solution. After another 4 hours, the saturated NaHCO3 solution was slowly added to adjust the pH of the tanning liquid to 4.0. Then the water bath was heated to 40 ℃, and the three-necked flask was soaked in the water bath for 2 hours. Finally, the tanned leather powder was washed alternately with deionized water and ethanol, and dried at 40 ℃ to obtain the chromium-titanium bimetallic leather powder.
[0043] (2) Five portions of chromium-titanium bimetallic powder were evenly placed in an alumina crucible, and then placed in a tube furnace. In a N2 atmosphere, the crucible was heated to 400 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling to room temperature, the pre-carbonized biochar was placed in a beaker, and a 4 mol / L KOH solution with a weight of 4 times that of the biochar was added. The mixture was stirred for 3 h and dried at 60 °C. In a nitrogen atmosphere, the dried solid was heated to 800 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling, it was washed with water to a neutral pH and dried to obtain the Cr2O3 / TiO2 / BC catalyst.
[0044] Example 2: Preparation of Cr2O3 / TiO2 / BC catalyst
[0045] (1) Take 20 parts of chromium sulfate and 37 parts of titanium sulfate (molar ratio 1:1.75) and dissolve them in deionized water. Then add 3 parts of sodium formate as a masking agent. Add formic acid and sodium bisulfite solution to adjust the pH to 2.0-3.0. Stir the reaction at 50-70 °C for 1-2 h and dry to obtain a chromium-titanium coordination compound.
[0046] 15 parts of leather powder and 300 parts of deionized water were added to a three-necked flask and soaked for 12 hours. 30 parts of chromium-titanium coordination compound were completely dissolved in 200 parts of water and then added to the three-necked flask. The three-necked flask was placed in a 30 ℃ water bath and stirred continuously. After soaking for 1 hour, the pH of the tanning liquid was immediately adjusted to 2.0 with a saturated NaHCO3 solution. After another 4 hours, the saturated NaHCO3 solution was slowly added to adjust the pH of the tanning liquid to 4.0. Then the water bath was heated to 40 ℃, and the three-necked flask was soaked in the water bath for 2 hours. Finally, the tanned leather powder was washed alternately with deionized water and ethanol, and dried at 40 ℃ to obtain the chromium-titanium bimetallic leather powder.
[0047] (2) Five portions of chromium-titanium bimetallic powder were evenly placed in an alumina crucible, and then placed in a tube furnace. In a N2 atmosphere, the crucible was heated to 400 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling to room temperature, the pre-carbonized biochar was placed in a beaker, and a 4 mol / L KOH solution with a weight of 4 times that of the biochar was added. The mixture was stirred for 3 h and dried at 60 °C. In a nitrogen atmosphere, the dried solid was heated to 800 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling, it was washed with water to a neutral pH and dried to obtain the Cr2O3 / TiO2 / BC catalyst.
[0048] Example 3: Preparation of Cr2O3 / TiO2 / BC catalyst
[0049] (1) Take 20 parts of chromium sulfate and 53 parts of titanium sulfate (molar ratio 1:2.5) and dissolve them in deionized water. Then add 3 parts of sodium formate as a masking agent. Add formic acid and sodium bisulfite solution to adjust the pH to 2.0-3.0. Stir the reaction at 50-70 °C for 1-2 h and dry to obtain a chromium-titanium coordination compound.
[0050] 15 parts of leather powder and 300 parts of deionized water were added to a three-necked flask and soaked for 12 hours. 30 parts of chromium-titanium coordination compound were completely dissolved in 200 parts of water and then added to the three-necked flask. The three-necked flask was placed in a 30 ℃ water bath and stirred continuously. After soaking for 1 hour, the pH of the tanning liquid was immediately adjusted to 2.0 with a saturated NaHCO3 solution. After another 4 hours, the saturated NaHCO3 solution was slowly added to adjust the pH of the tanning liquid to 4.0. Then the water bath was heated to 40 ℃, and the three-necked flask was soaked in the water bath for 2 hours. Finally, the tanned leather powder was washed alternately with deionized water and ethanol, and dried at 40 ℃ to obtain the chromium-titanium bimetallic leather powder.
[0051] (2) Five portions of chromium-titanium bimetallic powder were evenly placed in an alumina crucible, and then placed in a tube furnace. In a N2 atmosphere, the crucible was heated to 400 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling to room temperature, the pre-carbonized biochar was placed in a beaker, and a 4 mol / L KOH solution with a weight of 4 times that of the biochar was added. The mixture was stirred for 3 h and dried at 60 °C. In a nitrogen atmosphere, the dried solid was heated to 800 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling, it was washed with water to a neutral pH and dried to obtain the Cr2O3 / TiO2 / BC catalyst.
[0052] Comparative Example 1: Preparation of Cr@Ti / BC catalyst
[0053] Compared with Example 3, the only difference is that the method of loading the chromium-titanium complex on the leather powder is replaced by loading chromium and titanium in equal molar ratios on the leather powder respectively. The specific method is:
[0054] (1) Add 15 parts of leather powder and 300 parts of deionized water to a three-necked flask and soak for 12 hours. After 8 parts of chromium sulfate is completely dissolved in 100 parts of water, add it to the three-necked flask. Place the three-necked flask in a 30 ℃ water bath and stir continuously. After soaking for 1 hour, immediately adjust the pH of the tanning liquid to 2.0 with saturated NaHCO3 solution. After 4 hours, continue to slowly add saturated NaHCO3 solution to adjust the pH of the tanning liquid to 4.0. After 22 parts of titanium sulfate is completely dissolved in 100 parts of water, add it to the three-necked flask, continue to slowly add saturated NaHCO3 solution to adjust the pH of the tanning liquid to 4.0, then heat the water bath to 40 ℃ and soak the three-necked flask in the water bath for 2 hours. Finally, wash the tanned leather powder alternately with deionized water and ethanol, and dry it at 40 ℃ to obtain leather powder loaded with chromium and titanium.
[0055] (2) Five portions of chromium-titanium loaded skin powder were evenly placed in an alumina crucible, and then placed in a tube furnace. In a N2 atmosphere, the crucible was heated to 400 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling to room temperature, the pre-carbonized biochar was placed in a beaker, and a 4 mol / L KOH solution with a weight of 4 times that of the biochar was added. The mixture was stirred for 3 h and dried at 60 °C. In a nitrogen atmosphere, the dried solid was heated to 800 °C at a heating rate of 5 °C / min and kept warm for 2 h. After cooling, it was washed with water to a neutral pH and dried to obtain the Cr@Ti / BC catalyst.
[0056] Test example
[0057] Cr2O3 / TiO2 / BC-1, Cr2O3 / TiO2 / BC-2, and Cr2O3 / TiO2 / BC-3 represent the composite photocatalysts prepared in Examples 1-3, respectively.
[0058] (1) SEM characterization
[0059] Figure 1 The SEM images of the three materials (ac) are Cr2O3 / TiO2 / BC-1, Cr2O3 / TiO2 / BC-2, and Cr2O3 / TiO2 / BC-3. It can be seen from the figure that the structures of the three materials are relatively loose, with more holes and more active sites, so they have a larger contact area with the reactants, high degradation efficiency for tetracycline, and strong photocatalytic performance.
[0060] (2) BET characterization
[0061] Figure 2 The BET diagrams of Cr2O3 / TiO2 / BC-1, Cr2O3 / TiO2 / BC-2, and Cr2O3 / TiO2 / BC-3 show that the adsorption isotherm belongs to type IV isotherm, the hysteresis loop belongs to type H4, the isotherm has no obvious saturated adsorption platform, the pore structure is very irregular, and it has the typical adsorption-desorption characteristics of mesoporous materials. The specific surface areas of the three materials calculated by the N2 adsorption-desorption formula are 277.47 m 2 / g, 321.69 m 2 / g, 329.43 m 2 / g. The high specific surface areas of the three materials are conducive to the full contact between the composite material and TC and the absorption of light, while exposing more reactive active sites and promoting the degradation of TC.
[0062] (3) XRD characterization
[0063] Figure 3The XRD patterns of three materials, Cr2O3 / TiO2 / BC-1, Cr2O3 / TiO2 / BC-2, and Cr2O3 / TiO2 / BC-3, were used to analyze the crystal structure of the composite materials. As shown in the figure, similar diffraction peaks can be observed in the three composite materials with different Ti loading amounts. According to the picture, the diffraction peak at 2θ=12.8° corresponds to the (011) crystal plane, indicating the presence of highly dispersed amorphous carbon. The diffraction peaks at 2θ=25.5°, 36.2°, 41.3°, 48.3°, 56.7°, 62.8°, and 64.4° correspond to the (101), (101), (111), (200), (220), (204), and (310) crystal planes, respectively, which are the characteristic peaks of Cr2O3 and TiO2 crystals, respectively, confirming that the Cr2O3 / TiO2 / BC composite material was successfully synthesized in the experiment.
[0064] (4) PL analysis
[0065] The results of fluorescence spectroscopy performance test (PL) are as follows Figure 4 As shown. In the fluorescence spectrum performance test, the weaker the fluorescence intensity, the lower the recombination rate of photogenerated carriers. From the results, we can see that the fluorescence intensity of the three prepared Cr2O3 / TiO2 / BC materials is low, which indicates that the recombination rate of photogenerated carriers of the three materials is very low and has strong photocatalytic activity.
[0066] (5) Photocatalytic degradation of tetracycline (TC)
[0067] The activity of pure TiO2 and the Cr2O3 / TiO2 / BC composite photocatalyst prepared in Examples 1 to 3 was tested respectively, the target pollutant was TC solution, and the test conditions were as follows:
[0068] The initial concentration of TC solution was 50 mg / L, the dosage was 50 mL, the dosage of catalyst was 0.04 g, and a 500 W xenon lamp was used as the light source. During the experiment, the catalyst and TC solution were stirred in the dark for 10 min. After reaching the adsorption-desorption equilibrium, the light source was turned on to carry out the photocatalytic reaction. Samples were taken every 5 min and filtered to obtain the samples. The concentration of TC solution was measured by UV-visible spectroscopy. The degradation effect of TC solution was judged by Ct / C0. Among them, C0 is the initial concentration of TC solution, and Ct is the concentration of TC solution at reaction time t. The results are as follows: Figure 5 shown.
[0069] from Figure 5It can be seen that the degradation rates of pure TiO2, Cr2O3 / TiO2 / BC-1, Cr2O3 / TiO2 / BC-2 and Cr2O3 / TiO2 / BC-3 in 40 min are 49.13%, 88.3%, 88.6% and 94.2%, respectively. Compared with pure TiO2, the Cr2O3 / TiO2 / BC composite catalyst has a better photocatalytic degradation effect on TC.
[0070] (5) Stability test of Cr2O3 / TiO2 / BC-3
[0071] Cr2O3 / TiO2 / BC-3 and Cr@Ti / BC in comparative example 1 were used for cycle experiments. The cycle test conditions were the same as those in the activity test in (4), with 40 min as one cycle. After each cycle, the photocatalyst was directly recovered for the next cycle test, and a total of 3 cycles were performed. Figure 6 It can be seen that the degradation rates of TC by Cr@Ti / BC in the three cycle experiments were 86.9%, 82.2% and 73.1% respectively, and the degradation effect gradually decreased. However, the effect of TC photodegradation by Cr2O3 / TiO2 / BC-3 basically did not decay. After three cycles, the degradation rate was about 94%, which has better cycle stability, indicating that the material structure is relatively stable.
[0072] It can be seen from the above experimental results that the Cr2O3 / TiO2 / BC composite photocatalyst prepared by the embodiment of the present invention has greatly improved the loading stability of chromium and titanium bimetallics, has a large specific surface area, greatly increases the contact area between the photocatalyst and pollutants, and significantly reduces the recombination rate of photogenerated electron-hole pairs, thereby significantly improving the treatment capacity for pollutants.
[0073] To sum up, without violating the creative ideas of the present invention, any combination of the various embodiments of the present invention should be regarded as the contents disclosed by the present invention; within the technical concept of the present invention, any combination of various simple modifications of the technical scheme and different embodiments that do not violate the creative ideas of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a Cr2O3 / TiO2 / BC photocatalyst, characterized in that: The following steps are involved: After dissolving chromium sulfate and titanium sulfate, sodium formate is added, and the pH is adjusted to 2.0-3.0, and the mixture is reacted at 50-70° C. for 1-2 hours, and dried to obtain a chromium-titanium coordination compound; the molar ratio of the chromium sulfate, titanium sulfate and sodium formate is 1:(1-2.5):(0.2-1); Adding a chromium-titanium coordination compound to the pretreated leather powder for tanning, washing and drying the tanned leather powder to obtain a chromium-titanium bimetallic leather powder; as well as The chromium-titanium bimetallic powder is placed in an inert gas atmosphere for two pyrolysis steps, and then washed and dried; Among them, leather powder is made by crushing untanned waste leather scraps.
2. The preparation method according to claim 1, characterized in that The method for pretreating the leather powder is as follows: soaking the leather powder in deionized water for 6 to 12 hours to obtain a leather powder mixed solution.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the leather powder to the chromium-titanium coordination compound is 1:(1-2.7).
4. The preparation method according to claim 1, characterized in that: The specific method of performing the two pyrolysis is: placing the loaded chromium-titanium bimetallic skin powder in an inert gas atmosphere at 300-500°C for 2h, and after activation treatment, pyrolyzing it at 700-900°C for 2h.
5. The preparation method according to claim 4, characterized in that: Use 2~4mol / L KOH solution for activation treatment.
6. The preparation method according to claim 1, characterized in that: The tanning temperature is 30-40°C, the tanning time is 2-4h, and the pH is 3.5-4.
5.
7. The preparation method according to claim 1, characterized in that: The tanned leather powder was washed with deionized water and ethanol alternately and dried at 30-40°C.
8. The Cr2O3 / TiO2 / BC photocatalyst obtained by the preparation method as described in any one of claims 1 to 7.
Citation Information
Patent Citations
TiO2 / Cr2O3 / C nano material and preparation method thereof
CN110665492A
Method for preparing persulfate catalyst from waste chromium-containing leather shavings and application of persulfate catalyst
CN113398916A